Quantitative EEG Findings in Post-Stroke Epilepsy Patients - Ramli, Yetty (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2024)
Post-stroke epilepsy presents a significant clinical challenge, often accompanied by cognitive impairments. The qEEG analysis in this case reveals notable abnormalities, including increased delta waves and decreased high-frequency activity, localized to specific brain regions. These findings not only strengthen diagnostic assessments but also provide valuable insights into the underlying pathophysiology of post-stroke epilepsy. Moreover, they serve as a basis for selecting personalized therapeutic interventions, such as neurofeedback therapy. By tailoring treatment to the captured brainwave frequencies during recording, non-invasive therapeutic options can be explored as viable alternatives for patients. Integrating qEEG findings into clinical practice enhances our understanding of post-stroke epilepsy's complex nature and guides optimal patient care and management strategies.